STAT3 Inhibitors: A Novel Insight for Anticancer Therapy of Pancreatic Cancer - Xin Li; Wenkai Jiang; Shi Dong; Wancheng Li; Weixiong Zhu; Wence Zhou (Biomolecules, 2022)
The signal transducer and activator of transcription (STAT) is a family of intracellular cytoplasmic transcription factors involved in many biological functions in mammalian signal transduction. Among them, STAT3 is involved in cell proliferation, differentiation, apoptosis, and inflammatory responses. Despite the advances in the treatment of pancreatic cancer in the past decade, the prognosis for patients with pancreatic cancer remains poor. STAT3 has been shown to play a pro-cancer role in a variety of cancers, and inhibitors of STAT3 are used in pre-clinical and clinical studies. We reviewed the relationship between STAT3 and pancreatic cancer and the latest results on the use of STAT3 inhibitors in pancreatic cancer, with the aim of providing insights and ideas around STAT3 inhibitors for a new generation of chemotherapeutic modalities for pancreatic cancer.